Recovery of gelatin from poultry waste: Characteristics of the gelatin and lotus starch-based coating material and its application in shelf-life enhancement of fresh cherry tomato. (March 2022) - Rather, Jahangir A.; Makroo, Hilal A.; Showkat, Qazi A.; Majid, Darakshan; Dar, B.N.
Abstract: In recent years, food packaging has advanced from contaminating and polluting waste that remains after the use of the food product towards a functional ingredient that can be consumed along with the food product. Edible coatings are a healthy substitute for traditional food packaging. Therefore, the present study was aimed to develop edible coating material based on poultry waste gelatin and lotus stem starch for shelf-life extension of cherry tomatoes. The recovery of gelatin from chicken Feet (CF) and starch from lotus stem waste (LSW) was 14.5% and 9.20%, respectively and were used in different proportions for the development of the coating material. The flow behavior of coating material was pseudoplastic as the flow index ( n ) ranged from 0.332 to 0.428. The consistency coefficient ( k ) ranged from 1.62 to 4.92 Pa.s n, and it increased with the starch concentration. Storage modulus decreased with changing temperature from 10 °C to 25 °C and 10–35 °C in starch-free and starch-containing solutions, respectively. FTIR transmission band shifted from 3313 to 3343 cm −1 with changing the starch concentration from 0% to 10%, indicating the strong interactions of OH and amino groups. The transmission of UV light was low and remained unaffected, however, the transmittance showed a decrease with the starch concentration in the entire visible light range. The firmness and pH were retained to a greater extent and the weight loss in tomatoes was minimized during the 15 days of storage. The study revealed that this coating material may have great potential in the shelf-life extension of fresh fruits and vegetables. Graphical Abstract: ga1 Highlights: Poultry waste gelatin and starch-based coating materials were developed. Shear-thinning material with a consistency coefficient (k) of 1.62–4.92 Pa.sn was obtained. The bonding between starch and gelatin amino groups increased with starch concentration. The thermal stability and light transmittance gets highly affected by the amount of starch. The shelf-life of cherry tomatoes was enhanced up to 15 days by applying the edible coating.